Corporate Profit Shifting and the Multinational Enterprise - Stuart Webber (Copenhagen Business School (CBS), 2012)
This dissertation analyzes ways in which Multinational Enterprises (MNEs) shift profits from one country to another to reduce their income tax expense. This is an important topic for a number of reasons. From a country's perspective, its income tax rates and policies can have a significant impact upon its tax revenue, economic competitiveness, and the vibrancy of its economy. From the MNE's perspective, income tax rates and policies determine a firm's tax obligations, and thus affect net income and enterprise value. The dissertation examines several ways in which MNEs shift profits to reduce income taxes, and consists of five chapters. The introductory chapter reviews the economic evidence demonstrating firms shift profits from one country to another in response to tax rates. In the past two decades a number of economic studies have shown firms use tax and accounting techniques to shift reported profits to low tax jurisdictions, and that chapter reviews key articles that have demonstrated this. The second paper explains how MNEs finance international investments to shift interest income to low-tax jurisdictions. It reviews government tax policies in a number of countries that have been enacted to limit interest income shifting, and recommends an approach to control this activity. The third paper examines tax efficient supply chains, in which tax departments and supply chain organizations collaborate to site business operations to achieve supply chain objectives and reduce tax obligations. The fourth chapter analyzes how some U.S.-headquartered firms have moved their corporate headquarters from the U.S. to tax havens, to reduce their tax expense and avoid U.S. international tax policies. The fifth and final chapter examines new U.S. tax regulations that propose to value intellectual property transfers in the same way outside investors would, which the U.S. Internal Revenue Service (IRS) calls its “investor model.” It also makes recommendations concerning how the investor model can be improved.
hdl:10398/8457
Keywords: 650